2002
DOI: 10.1007/s00223-001-2109-4
|View full text |Cite
|
Sign up to set email alerts
|

Greater Trunk Muscle Torque Reduces Postmenopausal Bone Loss at the Spine Independently of Age, Body Size, and Vitamin D Receptor Genotype in Japanese Women

Abstract: Bone mineral density (BMD) is affected by muscle strength. Recently, vitamin D receptor (VDR) genotype was reported to affect muscle strength as well as BMD in Caucasian women. The aim of this study was to evaluate independent effects of muscle strength of the trunk on BMD at the spine and its change over time in Japanese women. We followed 119 healthy postmenopausal women for 4 years and determined the change in BMD at the spine by dual energy X-ray absorptiometry. Isometric peak torque and isokinetic concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 0 publications
1
25
0
3
Order By: Relevance
“…[37][38][39] Now, for the first time, we show that trunk muscle strength is independently associated with lumbar spine BMD in PD patients. The positive association between trunk muscle strength and lumbar spine BMD could be explained by the local biomechanical effects exerted by the muscles on bone tissue.…”
Section: Discussion Trunk Muscle Strength-bone Linkmentioning
confidence: 95%
“…[37][38][39] Now, for the first time, we show that trunk muscle strength is independently associated with lumbar spine BMD in PD patients. The positive association between trunk muscle strength and lumbar spine BMD could be explained by the local biomechanical effects exerted by the muscles on bone tissue.…”
Section: Discussion Trunk Muscle Strength-bone Linkmentioning
confidence: 95%
“…Studies have demonstrated that spine extensor muscle weakness is associated with low spine bone mineral density (BMD), (1,2) and spine deformity. (3) However, there are differing results regarding whether knee extensor strength is an independent predictor of BMD.…”
Section: Introductionmentioning
confidence: 99%
“…Most experts agree that there are two types of exercises that provide the most bone benefits: weightbearing exercises and strength-training (or resistance) exercises. Iki found a relationship between the trunk muscle strength and BMD exists independent of age, body size, dietary calcium intake, and the vitamin D receptor (VDR) genotype in postmenopausal Japanese women [30]. Also, Dixon found that in elderly women low grip strength was a marker of low BMD at both the spine and hip; low grip strength in women was associated with an increased risk of incident vertebral fracture [31].…”
Section: Discussionmentioning
confidence: 97%